Pengaruh Csr Disclosure Terhadap Firm Performance Dengan Corporate Reputation Sebagai Variabel Mediasi - Caroline Nathania; Adetya Krisnanda; Juniarti Juniarti (Business Accounting Review, 2020)
This study aims to know the effect of CSR Disclosure on Firm Performance with Corporate Reputation as mediation variable. In this study, CSR Disclosure measured by CSR index which refers to GRI G4 standards, Corporate Reputation measured by CII (Corporate Image Index) which conducted by Frontier Consulting Group, and Firm Performance measured by ROA. Furthermore, this study also uses Firm Size and Leverage as control variables.  This study uses 50 companies which listed in Indonesia’s Most Admired Company and disclosed their CSR activities in 2015-2019. The results of this study showed that CSRD had significant effect to Corporate Reputation, CSRD had significant effect to Firm Performance, Corporate Reputation had significant effect to Firm Performance. Furthermore, Corporate Reputation successsfully mediates CSRD against Firm Performance.